Modelling the Dispersion of Seafloor Massive Sulphide Mining Plumes in the Mid Atlantic Ridge Around the Azores - Morato, Telmo; Juliano, Manuela; Pham, Christopher K.; Carreiro-Silva, Marina; Martins, Inês; Colaço, Ana (Frontiers in Marine Science, 2022)
It is increasingly recognised that deep-sea mining of seafloor massive sulphides (SMS) could become an important source of mineral resources. These operations will remove the targeted substrate and produce potentially toxic plumes from in situ seabed excavation and from the return water pumped back down to the seafloor. However, the spatial extent of the impact of deep-sea mining is still uncertain because few field experiments and models of plume dispersion have been conducted. In this study, we used three-dimensional hydrodynamic models of the Azores region together with a theoretical commercial mining operation of polymetallic SMS to simulate the potential dispersal of plumes originating from different phases of mining operations, and to assess the magnitude of potential impacts. Although the model simulations presented here were subject to many caveats, they did reveal some important patterns. The model projected marked differences among sites making generalisations about plume-dispersal patterns in mid-ocean ridges difficult. Nevertheless, the models predicted large horizontal and vertical plume-dispersals above the thresholds adopted. Persistent plumes (temporal frequency >50%, i.e., 6 months out of 12 months) were projected to disperse an average linear distance of 10 to 20 km, cover an area of 17 to 150 km2, and extend more than 800 m in the water column. In fact, the model projected that plumes may disperse beyond the licensed mining areas, reach the flanks and summits of nearby topographic features, and extend into the bathypelagic, mesopelagic, and epipelagic environments. Modelled plume-dispersal overlaps with the predicted distribution of cold-water corals and with existing fishing activities. These potential impacts would be of particular concern in regions such as the Azores, where local populations are highly dependent on the sea for their livelihoods. The findings of this study are an important initial step towards understanding the nature and magnitude of deep-sea mining impacts in space and time.